Pengaruh Pendampingan Pada Ibu Bersalin & Pendamping Persalinan Terhadap Keberhasilan IMD - Indrasari, Nelly; Nurlaila, Nurlaila; Putriana, Yeyen (MIDWIFERY JOURNAL, 2023)
Breast milk is the gold standard baby food, breast milk is proven to have advantages that cannot be replaced by any food or drink, because breast milk contains the most appropriate, complete nutrients and always adapts to the baby's needs at all times. The gold standard for baby food begins with Early Breastfeeding Initiation (IMD), followed by exclusive breastfeeding for 6 (six) months (Munzia, 2013). According to data, only 3.7% of babies in Indonesia are breastfed within the first hour after birth. The failure of mothers to breastfeed their babies until the age of six months is actually just one problem, mothers do not fully understand how to breastfeed properly, including techniques and how to obtain breast milk, especially when they have to work. Understanding IMD is a very important issue. It is possible to implement IMD if individuals, families, health workers and the community already understand the meaning, benefits and objectives of IMD (Munzia, 2013). The results of Riskesdas (2018) stated that the rate of exclusive breastfeeding for 6 month old babies in Lampung Province reached 37.3% of the target of 60%. Meanwhile, in West Tulang Bawang Regency, the achievement of exclusive breastfeeding is 29.1% of the target of 60%, the achievement of IMD > 1 hour is 1.8% and IMD < 1 hour is 39.6%, which should be carried out on all newborn babies. (Riskesdas, 2018). The aim of the research is to determine the influence of assistance to mothers in labor & birth companions on the success of IMD in the PMB in the West Tulang Bawang Regency Service Work Area in 2022. This research uses a quasi experiment with control group design. The population in this study were all birth attendants and birth mothers in the work area of the West Tulang Bawang District Health Service in 2022. The sample for this study was birth attendants and birth mothers in the work area of the West Tulang Bawang District Health Service in 2022, totaling 96 people. Data was collected by means of documentation studies, interviews and observations. Data is processed and analyzed with descriptive and analytical statistics. The results of data processing show that the average IMD success in the intervention group was in the second 30 minutes, while for the control group there were 7 respondents who failed IMD and the rest succeeded IMD in the third 30 minutes. On average, respondents who were given assistance 3 times or more were successful in carrying out IMD in the first 30 minutes. Those who were given assistance 1-2 times managed to carry out the IMD in the second 30 minutes. Meanwhile, respondents in the control group (no assistance) on average succeeded in carrying out IMD in the 3rd 30 minutes. The results of statistical tests obtained a value of p=0.002, it can be concluded that there is a significant influence if assistance is provided by birth attendants on the success of IMD in mothers giving birth. Keywords:  Assistance, Early Breastfeeding Initiation (IMD)  ABSTRAK ASI merupakan makanan bayi dengan standard emas, ASI terbukti mempunyai keunggulan yang tidak dapat digantikan oleh makanan dan minuman apapun, karena ASI mengandung zat gizi paling tepat, lengkap, dan selalu menyesuaikan dengan kebutuhan bayi setiap saat. Standar emas makanan bayi dimulai dengan tindakan Inisiasi Menyusu Dini (IMD), dilanjutkan dengan pemberian ASI secara eksklusif selama 6 (enam) bulan (Munzia, 2013). Menurut data hanya 3,7 % bayi di Indonesia disusui dalam 1 jam pertama setelah kelahiran. Ketidakberhasilan ibu menyusui bayinya sampai usia enam bulan, sebenarnya hanya satu masalah, yaitu ibu belum memahami sepenuhnya cara menyusui yang benar termasuk teknik dan cara memperoleh ASI terutama saat mereka harus bekerja. Pemahaman tentang IMD merupakan persoalan yang sangat penting. Yang memungkinkan terlaksanannya IMD apabila individu, keluarga, petugas kesehatan serta masyarakat sudah memahami tentang pengertian, manfaat, serta tujuan dari IMD (Munzia, 2013). Hasil Riskesdas (2018) menyatakan bahwa angka pemberian ASI eksklusif pada bayi berumur 6 bulan di Provinsi Lampung hanya mencapai 37,3% dari target sebesar 60%. Sedangkan di Kabupaten Tulang Bawang Barat untuk capaian pemberian ASI eksklusif, yaitu 29,1% dari target sebesar 60%, capaian IMD > 1 jam 1,8% dan IMD < 1 jam 39,6% yang seharusnya IMD dilakukan pada semua bayi baru lahir (Riskesdas, 2018). Tujuan penelitian diketahui pengaruh pendampingan pada ibu bersalin & pendamping persalinan terhadap keberhasilan IMD di PMB Wilayah Kerja Dinas Kabupaten Tulang Bawang Barat Tahun 2022. Penelitian ini menggunakan quasi experiment with control group design. Populasi dalam penelitian ini adalah semua pendamping persalinan dan Ibu Bersalin di wilayah kerja Dinas Kesehatan Kabupaten Tulang Bawang Barat tahun 2022. Sampel penelitian ini adalah pendamping persalinan dan Ibu Bersalin di wilayah kerja Dinas Kesehatan Kabupaten Tulang Bawang Barat tahun 2022 yang berjumlah 96 orang. Pengumpulan data dengan cara studi dokumentasi, wawancara, dan observasi. Data diolah dan di analisis dengan statistik deskriptif dan analitik. Hasil pengolahan data menunjukkan bahwa rata-rata keberhasilan IMD pada kelompok intervensi pada 30 menit kedua, sedangkan untuk kelompok kontrol terdapat 7 orang responden yang tidak berhasil IMD dan sisanya berhasil IMD di 30 menit ketiga. Rata-rata responden yang diberi pendampingan sebanyak 3 kali atau lebih berhasil melakukan IMD di 30 menit pertama. Untuk yang diberi pendampingan 1-2 kali berhasil mekakukan IMD di 30 menit kedua. Sedangkan responden yang menjadi kelompok kontrol (tidak dilakukan pendampingan) rata-rata berhasil melakukan IMD di 30 menit ke 3. Hasil uji statistik didapatkan nilai p=0,002, berarti dapat disimpulkan ada pengaruh yang signifikan jika dilakukan pendampingan pada pendamping persalinan terhadap keberhasilan IMD pada ibu bersalin.   Kata kunci: Pendampingan, Inisiasi Menyusu Dini (IMD)